Aerobic direct arylation polycondensation of N-perylenyl phenoxazine-based fluorescent conjugated polymers for highly sensitive and selective TNT explosives detection - Nguyen, Cam H.T.; Nguyen, Tam Huu; Nguyen, Thao P.L.; Le Tran, Hai; Luu, Tam Hoang; Tran, Chau Duc; Nguyen, Quoc-Thiet; Nguyen, Le-Thu T.; Yokozawa, Tsutomu; Nguyen, Ha Tran (Dyes and pigments, 2023)
The rapid response, sensitivity, and selectivity detection of nitroaromatic explosives are major concerns for global sustainable development in order to promptly prevent and monitor their harmful effects on the environment and human health. Several different methods based on different principles have been developed to trace the nitroaromatic compound such as the 2,4,6-trinitrotoluene (TNT) compound. Recently, explosive detecting sensors based on organic conjugated fluorescent materials have been one of the most emerging subjects due to their reliable detection methods as well as portable lightweight instruments. This work uses two novel red fluorescent conjugated polymers, poly(PHP-alt-3HT) and poly(PHP-r-3HT-r-BTz), based on N-peryleneyl phenoxazine (PHP) and 3-hexyl thiophene (3HT), and benzotriazole (BTz) was successfully synthesized via an aerobic condition by direct arylation polycondensation. The red-fluorescent chemosensor based on novel conjugated polymers performed a high sensitivity for TNT detection with fast response time and good selectivity compared to common interferences. Besides tracing of TNT in the solution phase, the polymers also reached significant fluorescence quenching in the solid state by testing on a paper strip with the detection of up to 10−12 M concentrations of TNT. Further, the TNT vapor detection experiment is also effective with the fluorescence changes after only 1 min. The red fluorescent conjugated polymers based on N-peryleneyl phenoxazine (PHP) and 3-hexyl thiophene (3HT), and benzotriazole (BTz) named poly(PHP-alt-3HT) and poly(PHP-alt-3HT) have been synthesized successfully via aerobic direct arylation polycondensation in air condition. The fluorescent conjugated polymers exhibited a high sensitivity and significant selectivity for tracing of explosive TNT compound. The conjugated polymer showed a high fluorescence quenching efficiency with the quenching constants Ksv as 1.1 × 104, 1.6 × 104 M−1, and the limit for TNT detection was determined to be 4.67 μM and 2.01 μM for poly(PHP-alt-3HT) and poly(PHP-r-3HT-r-BTz). [Display omitted] •Novel red fluorescent conjugated polymers were prepared via direct arylation polycondensation under aerobic conditions.•N-perylenyl phenoxazine-based polymers were used as red fluorescent chemosensors for explosives detection.•Chemosensor exhibited good sensitivity, selectivity, and rapid response for TNT.•The present strategy shows great potential application prospects.